Scoping review protocol: the use of telemedicine in providing opioid agonist treatment and related psychosocial supports. Issue 12 (4th December 2020) - Crowley, Des; Homeniuk, Robyn; Delargy, Ide
Abstract : Introduction: The global opioid-related disease burden is significant. Opioid agonist treatment (OAT) can be effective in reducing illicit opioid use and fatal overdose, and improving multiple health and social outcomes. Despite evidence for its effectiveness, there are significant deficits in OAT globally. COVID-19 has required rapid adaptation of remote models of healthcare. Telemedicine is not used routinely in OAT, and little is known about the current levels of use and effectiveness. The objective of this review is to describe models of telemedicine and their efficacy. Methods and analysis: This scoping review uses the review methodology described by Arksey and O'Malley and adapted by Levac et al . The search strategy developed by the medical librarian at the Irish College of General Practitioners in conjunction with the research team will involve five databases (PubMed, EMBASE, the Cochrane Library, PsycInfo and OpenGrey) and the hand searching of reference lists. A limited initial search of two databases will be completed to refine search terms, followed by a second comprehensive search using newly refined search terms of all databases and finally hand searching references of included studies. To be included, studies must report on remote ways of providing OAT (including assessment, induction and monitoring) or related psychosocial support; be published in English after 2010. Two researchers will independently screen titles, abstracts and full-text articles considered for inclusion. Data will be extracted onto an agreed template and will undergo a descriptive analysis of the contextual or process-oriented data and simple quantitative analysis using descriptive statistics. Ethics and dissemination: Research ethics approval is not required for this scoping review. The results of this scoping review will inform the development of a national remote model of OAT. The results will be published in peer-reviewed journals and presented at relevant conferences.